Selected social institutions and some values of Filipino senior high school students implications to social studies for national development - Baking, Rodolfo Yangco 1939- (1982)
The purpose of the study is to investigate and analyze the influence of selected social institutions, namely, the family, school or education, church or religion, business or economics, politics or government, peer associations and the mass media, on some values of senior high school students in the Metropolitan Manila Area. The study intends to determine the extent of the influence of scoial institutions on individual values which can assist educational planners in their search for a more effective social studies program.